"We Deal With Symptoms Rather Than Causes": Antipoverty Policy Making in Occupied Palestinian Territories. Issue 8 (17th November 2017) - Easton, Scott D.; Safadi, Najwa Sado; Hasson, Robert G.
ABSTRACT: Since the Palestinian National Authority assumed governance, antipoverty reforms implemented to combat social problems and traumatic stressors have had limited success. Few empirical studies have investigated policy-making obstacles in this context. Using a social protection framework, this study examined the policy-making environment in Occupied Palestinian Territories. Data were collected through semistructured interviews with Palestinian ministry officials and archival records. Findings revealed a restrictive, obstacle-ridden environment that severely constrains development of high-quality policies for meeting needs of Palestinian citizens. Some limitations were similar to those in other emerging nations; others were unique to the case of Palestine. Policy and research implications are discussed.